Hubungan Penggunaan Gadget dengan Kualitas Tidur pada Mahasiswa Ekstensi Fakultas Kesehatan Masyarakat Indonesia - Ajeng Kusumawardani; Cynthia Yolanda (Yayasan Literasi Sains Indonesia, 2023)
In today's era of globalization, the development of technology, information, and communication is developing so rapidly, so that it can affect all aspects of social life and social interaction in society. The sophistication of technology, information, and communication is growing rapidly along with the development of human needs and an increasingly practical human lifestyle. Gadgets are a modern tool with various applications contained in it such as news, social media, information to various types of entertainment. Gadgets have many benefits, including communication and access to information becoming easier, entertainment facilities and means of increasing knowledge. Knowing the relationship between gadget use and sleep quality in extension students of the Faculty of Public Health, University of Indonesia. The design of this study uses a cross-sectional approach using quantitative data with Â student respondents extension the Faculty of Public Health, University of Indonesia with the academic status of active students. Data analysis in this study used a chi-square test with a CI of 95%. The results of using gadgets in the moderate category with poor sleep quality were 105 (93.8%) respondents. There is a significant relationship between gadget use and sleep quality in S1 extension students of the Faculty of Public Health, University of Indonesia (P-Value = 0.001).